Social cognitive systems in smart environments: Approaches for learning, reasoning, and adaptation - Aly, Amir; Pathak, Shashank; Andrist, Sean; Tacchella, Armando (Cognitive Systems Research, 2019)
Robot-Enabled Support of Daily Activities in Smart Home Environments